ANALISIS PENDAPATAN KERIPIK PISANG PADA INDUSTRI RUMAH TANGGA SOFIE DI KOTA PALU - Saleh, Rahmad (AGROTEKBIS, 2015)
This study aims to know the amount of income of banana chips in Industry Household Sofieof Palu City.  The Respondent is done intentionally (purposive) of 3 people. Data analysed using revenue analysis methode. The results showed that the average amount of revenue that theindustry Sofie Rp 3,626,666 per month with a total cost of Rp 2,631,969 so the average income earned Household Industrial Sofie in producing banana chips Rp 994 697 per month.